2012
DOI: 10.7314/apjcp.2012.13.5.1837
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-Based Therapy for the Treatment of Elderly Patients with Non-Small-Cell Lung Cancer: a Retrospective Analysis of a Single Institution

Abstract: Background: In spite of the fact that platinum-based doublets are considered the standard therapy for patients with advanced non-small-cell lung cancer (NSCLC), no elderly-specific platinum based prospective phase III regimen has been explored. The aim of this retrospective singlecenter study was to evaluate the efficacy and side effects of cisplatin-based therapy specifically for the elderly. Methods: Patients receiving platinum-based treatment were divided into three groups. In the first group (GC), Gemcitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The articles analyzed the efficacy of platinum, non-platinum or combination therapeutic regimens while also advocating towards specific treatment modalities. Nine studies advocate for combination therapy as an effective treatment regimen for first-line NSCLC [7][8][9][10][11][12][13][14][15], five studies advocate towards non-platinum based therapy as an effective and safer regimen [8,[16][17][18][19], one study concludes that non-platinum based therapy is an effective regimen compared to combination therapy in first-line NSCLC [20], two studies conclude that both non-platinum based regimens and combination therapy show an equal efficacy [21,22], three therapies indicate similar efficacy between platinum-based and non-platinum based regimens [23][24][25], two therapies indicate that the efficacy of non-platinum based therapy is similar to the efficacy of other treatment regimens [26,27], one study states that platinum-based regimens showed a higher efficacy and response rate than non-platinum based regimens [28], 12 studies advocate for non-platinum based regimens as a second line treatment regimen [29][30][31][32][33][34][35][36][37][38][39][40], and two studies advocate towards combination therapy for second-line treatment [41,42]. Most of the articles lean towards the use of combination therapy for first-line treatment and non-platinum based therapy for second-line treatment.…”
Section: A Brief Analysis Of Resultsmentioning
confidence: 99%
“…The articles analyzed the efficacy of platinum, non-platinum or combination therapeutic regimens while also advocating towards specific treatment modalities. Nine studies advocate for combination therapy as an effective treatment regimen for first-line NSCLC [7][8][9][10][11][12][13][14][15], five studies advocate towards non-platinum based therapy as an effective and safer regimen [8,[16][17][18][19], one study concludes that non-platinum based therapy is an effective regimen compared to combination therapy in first-line NSCLC [20], two studies conclude that both non-platinum based regimens and combination therapy show an equal efficacy [21,22], three therapies indicate similar efficacy between platinum-based and non-platinum based regimens [23][24][25], two therapies indicate that the efficacy of non-platinum based therapy is similar to the efficacy of other treatment regimens [26,27], one study states that platinum-based regimens showed a higher efficacy and response rate than non-platinum based regimens [28], 12 studies advocate for non-platinum based regimens as a second line treatment regimen [29][30][31][32][33][34][35][36][37][38][39][40], and two studies advocate towards combination therapy for second-line treatment [41,42]. Most of the articles lean towards the use of combination therapy for first-line treatment and non-platinum based therapy for second-line treatment.…”
Section: A Brief Analysis Of Resultsmentioning
confidence: 99%
“…Although multiple, older adult-specific clinical trials with gemcitabine have reported a manageable hematologic toxicity profile [23][24][25][26], clinical trials in older adults receiving platinum-doublet remain scarce and difficult to extrapolate because of divergent treatment regimens and geriatric patient populations [2,[27][28][29]. Comparative analyses of hematologic toxicity in clinical trials including both geriatric and nongeriatric patients showed conflicting results [8,30].…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the control group will receive mainline treatments of platinum-based doublet chemotherapy (GP, TP, or DP). The three regimens have no statistically significant difference in the response rates, PFS, and OS [ 16 ]. A chemotherapy cycle is 21 or 28 days in length.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, large-scale clinical trials always exclude elderly patients with lung cancer [ 15 ]. As a result, there is little high-level or large-scale evidence from evidence-based medicine with a focus on the elderly with lung cancer [ 16 ]. Therefore, there is an urgent need to find a new effective therapy with less toxicity for the elderly with lung cancer.…”
Section: Introductionmentioning
confidence: 99%